Exploring Higher-Order Thinking Skills Integration in Mathematics Curriculum: A Study of Six Lebanese Schools - Edmond Khoury, Megan; Kandil, Bassem (International Research in Education, 2024)
This article investigates the promotion of higher-order thinking skills in the written curriculum of six diverse schools in Lebanon, focusing on Grades 1, 2, and 3 mathematics outcomes. The educational programs encompass the International Baccalaureate’s Primary Years Programme, the Lebanese National Curriculum, and the French National Curriculum. Employing Bloom’s Taxonomy (1956) as the theoretical framework, the study meticulously categorizes learning objectives into six cognitive domains, shedding light on the emphasis placed on lower and higher-order thinking skills. Results reveal nuanced patterns across schools and grade levels. In Grade 1, School 4 demonstrates a notable focus on “analyze,” while School 2 excels in “create.” Grade 2 highlights the International Baccalaureate’s Primary Years Programme, particularly School 2, for emphasizing the three higher domains of Bloom’s Taxonomy (1956). The Lebanese National Curriculum exhibits variations, with School 4 emphasizing “analyze.” This research holds significance amidst Lebanon’s educational challenges, marked by outdated curricula, declining academic performance, and recent disruptive events. The study advocates for a paradigm shift, emphasizing the need for comprehensive educational philosophies, curriculum revisions, and student-centered teaching approaches. The findings provide valuable insights for policymakers and educators to navigate the complexities of Lebanon’s educational landscape, fostering a transformative approach for resilient and innovative students amid challenging circumstances.